Call for Emergency Action to Limit Global Temperature Increases, Restore Biodiversity, and Protect Health: Wealthy Nations Must do Much More, Much Faster - Lukoye Atwoli (Ubiquity Press, 2021)
Joint editorial calling for emergency action to limit global temperature increases, restore biodiversity, and protect health.